REACTION OF CROPS ON SOIL POLLUTION WITH OIL - Kolesnikova, L.A.; Galytska М. А.; Pischalenko М. А.; Barabolia О. V.; Chubuk, D.I.; Litvishko, O. A. (Scientific Progress & Innovations, 2019)
The expediency of solving ecological problems concerning the pollution of farm lands with oil by deter-mining the toxic effect of different oil contamination levels on the resistance of crops, which are most widely spread in the region ( on the example of winter and spring wheat) was substantiated in the article. Attention is focused on the connection of oil contamination with changing plant anatomical-morphological indices according to dose –effect type. Separate problem aspects of the reasons of oil polluted soil phyto-toxicity, the effect on winter and spring wheat germination, their growth characteristics, and morphological changes in stress conditions were substantiated. The stimulating effect of oil contamination at a level of ≤5 мл/kg of soil was shown. The effect was manifested in activating seed germination and developing sprouts’ vegetative or-gans. Interrelation between crude oil content in the soil was revealed according to indices of environmental effect on test-crops. It has been established that winter wheat is more resistant to the influence of different levels of soil oil contamination concerning similarity and lamina parameters. Investigating the morphologi-cal manifestations of toxic properties of crude oil components on spring wheat sprouts was based on study-ing the dynamics of structural organization of functionally active green leaves; yellowing leaves; shrunken and dried-up leaves of perished plants. It has been revealed that a combined action of two similarly directed physical-chemical factors is the reason of phyto-toxicity in the conditions of considerable modeled soil oil contamination. These factors are: chemical – the toxicity of methane, oil aromatic hydrocarbons and physi-cal – increasing the acquired soil hydrophobia (water-repellent property), which considerably retards and stops the processes of gas and water exchange between the soil and plants, resulting in low seed germina-tion, sprouts’ growth inhibition, decreasing the amount of structural- fibrous bundles and chlorechyma in lamina, wheat destruction, drying-up, and mortality of wheat.